Smallholders’ avocado production systems and tree productivity in the southern highlands of Ethiopia - Biazin, B.; Haileslassie, Amare; Zewdie, T.; Mekasha, Yoseph; Gebremedhin, Berhanu; Fekadu, A.; Shewage, Tesfaye (Springer, 2018)
Ethiopia is one of the top five avocado producers in sub-Saharan Africa. Despite increasing recognition for its nutritional value and economic importance, information on smallholder avocado production systems across agro-climatic zones and determinants for tree productivity are literally lacking. Therefore, the objectives of this study were to examine the determinants for avocado tree holdings by smallholder farmers and investigate the effect of avocado production systems and management conditions on fruit yield by individual avocado trees in Southern Ethiopia. Data required for the study was collected through a combination of focus group discussions, household survey and field tree inventories. The data was analyzed using descriptive statistics, analyses of variance and linear regression methods using statistical software for social sciences (SPSS version 20). In the study region, avocado is mainly grown as an integral component of the coffee- and enset-based agroforestry systems. The number of avocado trees owned by smallholder producers was related to district, sex of household head, age of household head, educational status, land holding size, pest and disease damage and access to extension services. Productivity of avocado was significantly (p < 0.05) different between production systems. The highest avocado fruit yield was observed from trees grown in the coffee and enset-based agroforestry systems. However, the smallholder producers complain that the yields of coffee and enset grown under avocado trees could be very low. The total height of avocado trees was significantly (p < 0.05) different across the different production systems. The mean heights of matured (21–25 years old) avocado trees were 17.57 ± 0.86 m (±SE; N = 20) under coffee-based agroforestry system and 14.93 ± 1.24 m when grown as individual trees around homes. Proper extension support is needed to disseminate improved production techniques: encompassing proper tree spacing, tree training, pruning, soil amendments, growing optimum number of trees for successful pollination and improved harvesting.